2023
DOI: 10.1186/s40779-023-00468-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miRNA by CRISPR/Cas in cancer: advantages and challenges

Abstract: Clustered regulatory interspaced short palindromic repeats (CRISPR) has changed biomedical research and provided entirely new models to analyze every aspect of biomedical sciences during the last decade. In the study of cancer, the CRISPR/CRISPR-associated protein (Cas) system opens new avenues into issues that were once unknown in our knowledge of the noncoding genome, tumor heterogeneity, and precision medicines. CRISPR/Cas-based gene-editing technology now allows for the precise and permanent targeting of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 231 publications
0
6
0
Order By: Relevance
“…To inhibit miRNA activity, small-molecule inhibitors specific to certain miRNAs are also being developed. The second strategy, miRNA replacement, includes the reintroduction of tumor-suppressor miRNA mimics to restore the loss of function [ 149 , 150 , 151 , 152 ].…”
Section: Mirna-based Therapeutic Approaches To Breast Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To inhibit miRNA activity, small-molecule inhibitors specific to certain miRNAs are also being developed. The second strategy, miRNA replacement, includes the reintroduction of tumor-suppressor miRNA mimics to restore the loss of function [ 149 , 150 , 151 , 152 ].…”
Section: Mirna-based Therapeutic Approaches To Breast Cancer Treatmentmentioning
confidence: 99%
“…Synthetic miRNA mimics must be delivered efficiently for target cells for miRNA replacement therapy to be effective. There are a variety of delivery systems that can be used to ensure effective uptake by target tissues, including viral vectors, lipid nanoparticles, and other nanocarriers [ 150 , 151 , 152 , 170 ]. A synthetic miRNA mimic is incorporated into the RISC and acts similarly to endogenous miRNAs once inside a cell.…”
Section: Mirna-based Therapeutic Approaches To Breast Cancer Treatmentmentioning
confidence: 99%
“…Liposomes have many merits as gene delivery vectors. Firstly, liposomes are spherical vesicles that encapsulate nucleic acids and resist nucleases ( Hussen and Mahmud, 2023 ). Secondly, similar to cell membranes, liposomes are easy to fuse with recipient cells and have high transfection efficiency.…”
Section: Application Of Non-viral Vectors In Cardiovascular Diseasesmentioning
confidence: 99%
“…It is known that miRNAs belong to short, noncoding RNAs and modulate the gene expression [62]. Clearly, miRNAs have been reported to be involved in various diseases, including cancer [63][64][65]. One study showed that 37 miRNAs were differentially expressed in IgAN patients compared with healthy controls [66].…”
Section: Mirnas Regulate Glycosylation Of Iga1mentioning
confidence: 99%